The analysis of late postoperative complications after treatment of ureteral stones using ureteroscopy and contact ultrasonic lithotripsy - Антонян, Игорь Михайлович; Стецишин, Роман Васильевич; Рощин, Юрий Владимирович (ScienceRise: Medical Science, 2016)
Ureteroscopy is a highly effective and minimally invasive diagnostic and treatment technology. In association with intracorporeal lithotripsy, ureteroscopy is in the first line of distal ureteral stones treatment strategy. Methods. In 1034 patients with ureterolithiasis ureteroscopy with contact lithotripsy and (or) lithoextraction was carried out against different ureteral stones. The patients were examined after discharge in dynamics from 8 weeks to 1,5 years, and on the testimony - to the complications liquidation. All testimonies were divided according to their severity levels using Satava classification. Results. 90 patients with late postoperative complications were found. In 78 (86,7 %) of them transient vesicoureteral reflux, and in 12 (13,3 %) ureterostegnosis were found. In case of postoperative complications development, their clear dependence on stone density is noted in patients with stones size to 1 cm. The dependence is leveled with an increase in the stone size, and complications may occur at any concrement density. At concrement localization in the middle and upper third, the probability of the late postoperative complications development does not depend on stone size, but the complications significantly more often occur at stone size to 1 cm and more when it is localized in the lower ureter. The probability of the late postoperative complications increases when concrement density is 1000 HU and more regardless its localization